Interaksi Tradisi Jawa Dengan Nilai Islam: Tradisi Kawin Mayit Dalam Hukum Islam (Studi Kasus di Kecamatan Malo Kabupaten Bojonegoro) - Salamon, Dimas Abdul Fatah; Sallom, Dea Salma (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
Kawin mayit is a marriage ceremony conducted in the presence of a deceased parent's body when an engaged couple, whose engagement had been established, experiences the passing of one of the parents. Subsequently, the surviving partner and the deceased parent must solemnize their marriage vows in the presence of the deceased parent's body before it is interred. The aim of this research is to examine the reality of customary law in practice in Bojonegoro, East Java, and to analyze the compatibility of kawin mayit within Islamic law, as well as the Islamic values embedded within it. This study falls within the category of empirical research and employs a phenomenological approach. The results of this study indicate that the tradition of kawin mayit is carried out as a form of filial respect toward one's deceased parents. This practice holds inherent religious value in its observance. In Islamic law, there is no contradiction regarding the solemnization of marriage vows in the presence of a deceased body, as long as the conditions and essential elements of marriage are met. This practice can be aligned with the stance of the companions of the Prophet at the time of his passing.